The collected poetry of Carol Shields - Shields, Carol (McGill-Queen's University Press, 2021)
"Carol Shields, best known for her fiction writing, received both the Pulitzer Prize and the Governor General's Award for Fiction for her novel The Stone Diaries. But she also wrote hundreds of poems over the span of her career. The Collected Poetry of Carol Shields includes three previously published collections and over eighty unpublished poems, ranging from the early 1970s to Shields's death in 2003. In a detailed introduction and commentary, Nora Foster Stovel contextualizes these poems against the background of Shields's life and oeuvre and the traditions of twentieth-century poetry. She demonstrates how poetry influenced and informed Shields's novels; many of the poems, which constitute miniature narratives, illuminate Shields's fiction and serve as the testing ground for metaphors she later employed in her prose works. Stovel delineates Shields's career-long interest in character and setting, gender and class, self and other, actuality and numinousness, as well as revealing her subversive feminism, which became explicit in Reta Winter's angry (unsent) letters in Unless and in the stories of poet Mary Swann and Daisy Goodwill in Swann and The Stone Diaries. The first complete collection of her poetry, this volume is essential for all readers of Carol Shields. Stovel's detailed annotations, based on research in the Carol Shields fonds at Library and Archives Canada, reveal the poems in all their depth and resonance, and the dignity and consequence they afford to ordinary people."--